Даяаршлын нөхцөлд Монгол хэрхэн Монголоороо үлдэх вэ - Хүүхэнбаатар, Дашдаваа (Historia Mongolarum, 2003)
The article deals with the place of Mongolia in globalization era. Problems of survival of Mongolian nation and transhumanism in the globalization have been discussed in this article. The transhumanism was, that is, and should be essential part of our life. The maintainnace of our civilization is to obtain solid position in the world in new era.